Laminin concentration in ascites of patients with hepatic cirrhosis and peritoneal carcinomatosis - Catarino,R.M. (2005)
Laminin levels in ascitic fluid have been proposed as a marker for neoplastic ascites. We compared the concentration of laminin in serum and in ascitic fluid from patients with hepatic cirrhosis and peritoneal carcinomatosis and assessed the diagnostic value of serum laminin levels in differentiating neoplastic from benign ascites. Laminin concentrations were determined by ELISA with antibodies against laminin extracted from the human placenta, in patients with ascites due to peritoneal carcinomatosis (N = 20) and hepatic cirrhosis (N = 33). Patients with infected or hemorrhagic ascites were excluded. The receiver operating characteristic curve was used to determine the sensitivity and specificity of serum laminin for the diagnosis of neoplastic ascites. When compared to the group with cirrhosis, the carcinomatosis group presented significantly higher mean laminin levels in serum (3.3 ± 0.5 vs 2.1 ± 0.4 µg/ml, mean ± SD, P < 0.05) and ascites (2.8 ± 0.5 vs 1.6 ± 0.4 µg/ml, P < 0.05). Although laminin concentration was higher in serum than in ascites, the laminin serum/ascites ratio and serum-ascites gradient did not differ between the studied groups. A significant correlation (r = 0.93, P < 0.0001) was observed between the serum and ascites laminin values. Serum laminin levels >2.25 µg/ml showed 100% sensitivity and 73% specificity for the diagnosis of neoplastic ascites. Serum concentration seems to be the main determinant of laminin levels in ascitic fluid and its values can be used as a diagnostic parameter in the study of neoplastic ascites.